KEBIJAKAN REDAKSIONAL DALAM PENAYANGAN PROGRAM ANAK DI TRANS7 - Oki Setiaji Dewanto (2010)
ABSTRACT Child program can become the efective communication, where child program have come to the model in the world of education to the fore, because in character which is visual audio can play role its as education media and media development of the talent is very effective for children. Attendance of child program in a news room is not without cause, but on the contrary that is attendance of child program in news room have the effect is big so in fulfilling the ambition of information from